Molecular Mapping of the RNA Cap 2′-O-Methyltransferase Activation Interface between Severe Acute Respiratory Syndrome Coronavirus nsp10 and nsp16 - Lugari, Adrien (American Society for Biochemistry and Molecular Biology, 2010)
Several protein-protein interactions within the SARS-CoV proteome have been identified, one of them being between non-structural proteins nsp10 and nsp16. In this work, we have mapped key residues on the nsp10 surface involved in this interaction. Alanine-scanning mutagenesis, bioinformatics, and molecular modeling were used to identify several “hot spots,” such as Val(42), Met(44), Ala(71), Lys(93), Gly(94), and Tyr(96), forming a continuous protein-protein surface of about 830 Å(2), bearing very conserved amino acids among coronaviruses. Because nsp16 carries RNA cap 2′-O-methyltransferase (2′O-MTase) activity only in the presence of its interacting partner nsp10 (Bouvet, M., Debarnot, C., Imbert, I., Selisko, B., Snijder, E. J., Canard, B., and Decroly, E. (2010) PLoS Pathog. 6, e1000863), functional consequences of mutations on this surface were evaluated biochemically. Most changes that disrupted the nsp10-nsp16 interaction without structural perturbations were shown to abrogate stimulation of nsp16 RNA cap 2′O-MTase activity. More strikingly, the Y96A mutation abrogates stimulation of nsp16 2′O-MTase activity, whereas Y96F overstimulates it. Thus, the nsp10-nsp16 interface may represent an attractive target for antivirals against human and animal pathogenic coronaviruses.